Proposal formula for the determination of the density of walls built with blocker II - Cotrado Flores, Dina Marlene (2020)
This project was carried out under the financing of the "VI Competition of financing for research projects Private University of Tacna (UPT)". In this project, tests have been carried out on the piles and the death of masonry, which were built using the masonry unit to block II of the Martorell brickyard. With the results of the essays and the compilation of other essays carried out by our university students, the values ​​of f'm and v'm have been determined. The base of all the studies has been elaborated a proposal of formula of the minimum density of the walls, which allows us to calculate the minimum length of the walls that is needed in a masonry building built with load-bearing walls of the blocker II so that it can resist a severe earthquake.